2008
DOI: 10.1007/s00253-007-1256-6
|View full text |Cite
|
Sign up to set email alerts
|

Biologically active components and nutraceuticals in the Monascus-fermented rice: a review

Abstract: Monascus-fermented rice has traditionally been used as a natural food colorant and food preservative of meat and fish for centuries. It has recently become a popular dietary supplement because of many of its bioactive constituents being discovered, including a series of active drug compounds, monacolins, indicated as the 3-hydroxy-3-methylglutaryl-coenzyme A reductase inhibitors for reducing serum cholesterol level. The controversy of its safety has been provoked because a mycotoxin, citrinin, is also produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
147
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(155 citation statements)
references
References 61 publications
1
147
1
1
Order By: Relevance
“…It was reported that there is shift in absorbance maxima of the pigment extract at different incubation temperatures (Carvalho et al, 2005). Reports also revealed that the optimum cultural conditions for Monascus purpureus pigment production is 3 days of incubation period at 32°C, and pH 6.0 (Lin et al, 2008). …”
Section: Effect Of Temperature On Biomass and Pigment Productionmentioning
confidence: 98%
“…It was reported that there is shift in absorbance maxima of the pigment extract at different incubation temperatures (Carvalho et al, 2005). Reports also revealed that the optimum cultural conditions for Monascus purpureus pigment production is 3 days of incubation period at 32°C, and pH 6.0 (Lin et al, 2008). …”
Section: Effect Of Temperature On Biomass and Pigment Productionmentioning
confidence: 98%
“…The Chinese Ministry of Health has incorporated Monascus pigments into their modern food additive standards to increase the colour and delicacy of meat, fish, and soybean products (Fabre et al 1993). Production, isolation, and purification of Monascus pigments have been extensively studied (Li et al 2004;Babitha et al 2007;Lin et al 2008;Zhang et al 2014). Monascus pigments include the following main compound types: ankaflavin and monascin (yellow); monascorubrin and rubropunctatin (orange); and monascorubramine and rubropuctamine (red) (Ma et al 2000;Heber et al 2001;Cheng et al 2011;Durakli-Velioğlu et al 2013).…”
Section: Doi: 1017221/430/2015-cjfsmentioning
confidence: 99%
“…Industrially, Monascus species is an important source of bioactive compounds like monacolin K, which is a very effective hypocholesterolemic agent. However, a toxic drug interaction has been reported between cyclosporine and monacolin K of the red yeast rice (Monascus purpureus) that led to rhabdomyolysis in a renal transplant recipient [6][7][8][9][10]. Some Monascus compounds such as citrinin have been reported to be nephron-hepatotoxic [8].…”
Section: Discussionmentioning
confidence: 99%